UJI POTENSI BAKTERI KITINOLITIK DALAM MENGHAMBAT PERTUMBUHAN Rhizoctonia solani PENYEBAB REBAH KECAMBAH PADA KENTANG VARIETAS GRANOLA - Dewi Novina; Dwi Suryanto; Elimasni D (Saintia Biologi, 2012)
A study on assay the potential of chitinolytic bacterial isolates to inhibit the growth of Rhizoctonia solani causal agent of damping-off on potato was carried out in Laboratory of Observation Pest and Disease, Medan Johor, UPT. Protection of Crops and Holticulture 1 and Laboratory of Microbiology, Department of Biology, Faculty of Mathematics and Natural Science of Universitas Sumatera Utara, Medan. Two out of six isolates of chitinolytic bacteria showed capabilities to inhibit of R. solani growth. The most effective isolates to inhibit the growth of R. solani were Enterobacter sp. BK15 and Bacillus sp. BK13, that were able with inhibition zone of 2.05 and 2.35 cm, respectively. These two isolates also showed to be able to reduce fungal infection by 31.25% and 37.5%, respectively. Keywords: Bacillus sp. BK13, damping-off, Enterobacter sp. BK15, R. solani, potato